Gallstone ileus: literature review - Artioli, Giulia; Muri, Margherita; Praticò, Francesco Emanuele; Marcantoni, Emanuele Angela; Gazzani, Silvia Eleonora; Lana, Silvia; Bacchini, Emanuele; Capretti, Giovanni; Muri, Maurizio; Torri, Tito (Acta Biomedica Atenei Parmensis, 2016)
Gallstone ileus is a rare case of mechanical intestinal obstruction observed in patients with history of cholelithiasis or cholecystitis. Its diagnosis is difficult and it is characterized by high mortality rate. Diagnostic Imaging plays an important role in the management of patients with suspected gallstone ileus because an early diagnosis could reduce the mortality. Abdominal Computed Tomography (CT) is the preferred modality because of its rapid diagnosis. Surgery remains the gold standard treatment.